Improving the Efficiency of Working With Modern Methods and Programs in Distance Learning of a Foreign Language - Baxtiyor qizi, Rustamova Gulnoza (European Journal of Life Safety and Stability (2660-9630), 2023)
With the development of technology, different ways and tools have been developed to help the people in our daily lives. The same is true in the world of education. For years now, e-learning has been included as a supplement to face-to-face classes. Online options were introduced as complements to traditional learning and changing and entirely online courses are being introduced. The same is happening with languages, in this field also online learning is proposed. In this article claim that the positive points of learning languages in online way. Teaching languages online is one of the most lucrative career options nowadays, especially as more and more people shift to remote work. It’s also one of the most fulfilling — you get to earn from teaching something you know while also helping language learners. However, if you’re new to the world of online teaching, the idea of starting from scratch may seem daunting. And even if you have a background in face-to-face teaching, shifting to an online career can still be unsettling.